Arabidopsis COPPER TRANSPORTER 1 undergoes degradation in a proteasome-dependent manner. (28th July 2020) - Li, Jinjin; Yuan, Jinhong; Wang, Hui; Zhang, Hui; Zhang, Haiyan
Abstract: The essential nutrient copper is toxic in excess. Therefore, plants must tightly control copper uptake and distribution. Arabidopsis thaliana high-affinity copper transporters (COPTs) mediate copper uptake, partitioning, and redistribution. Here we show that COPT1 localizes to the plasma membrane and endoplasmic reticulum in stably transgenic plants expressing a COPT1–green fluorescent protein (GFP) fusion protein, and the fusion protein is rapidly degraded upon plant exposure to excess copper. MG132 treatment largely abolished copper-induced degradation of COPT1, implying a link between the proteasome and COPT1 activity in modulating copper uptake. Co-immunoprecipitation analyses revealed that COPT1 cannot be ubiquitinated in the presence of excess copper and MG132. Through site-directed mutagenesis, we identified Lys159 in the C-terminal cytoplasmic tail of COPT1 as critical for copper acquisition, but not for copper-mediated down-regulation of COPT1, in plants. Furthermore, pharmacological analysis showed that treatment with a vesicle trafficking inhibitor or a V-ATPase inhibitor does not alter the subcellular dynamics of COPT1–GFP, consistent with the absence of a connection between the endosomal recycling/vacuolar system and COPT1 degradation. Together, our data suggest that proteasomal degradation rather than vacuolar proteolysis is important for the regulation of copper transport to maintain copper homeostasis in plants. Abstract : Arabidopsis COPT1 stability is modulated through the proteasomal degradation pathway bypassing endosomal vesicle trafficking, leading to a rapid adaptation of intracellular copper in response to extracellular excess copper.